A STUDY OF USING SOCIAL MEDIA AND INTERNET IN THE TRANSFORMATION OF THE STATE MUSEUM OF NEGERI SEMBILAN - shukri, Sakinah mohd; kKhatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to investigate the impact of social media and internet on transformation of state museum. Visitor’s intentional behaviour in creating perception and intention is an important factor for State Museum of Nigeria Sembilan in creating awareness and delivering history education using informal techniques. Emphasis on the importance of social media and internet information availability are now growing and becoming fast new market force in moving into mainstream market affecting and changing perception on how State Museum of Nigeria Sembilan should be conducted in delivering informal education in the visitor’s point of view. Yet, the concept of social media and internet as platform for marketing tools in transformation of Museum’s Nigeria Sembilan in term of service quality has not been given a clear practical foundation; and the antecedents and consequences of the concept of State Museum of Nigeria Sembilan, when manifest specific service context, have not been empirically explored. This research attempts to provide a first step towards establishing intentional behaviour basis for The State Museum of Nigeria Sembilan quality service, empirically testing its hypothesized antecedents, consequences and exploring the resulting implication as well as to explore the key elements dimension of visitor’s perception. There were 489 respondents chosen for the analysis. Managerial implication expected the consideration of whether The State Museum of Nigeria Sembilan services is a reasonable and meaningful visitor expression in particular service context, the necessity of focusing on surprising level of perception when attempting to predict decision making and potentially separate strategies for including experience and intention.